Upaya Guru PAI Membimbing Siswa Menghafal Al-Qur’an Tepat Waktu di SDI Al-Barokah Kramat Tlanakan Pamekasan - Fatimatus Zahrah (LPPM Politeknik Pratama, 2024)
The phenomenon that memorizing the Qur'an is increasingly being applied in Islamic educational institutions, including at SDI Al-Barokah pamekasan is an example of the progress of islam. The success of memorizing the Qur'an at SDI Al-Barokah is one of them determined by the guidance of the teacher who is specially prepared to guide the memorization. Therefore it is interesting to research scientifically about 1. How is the process of Islamic religious education teachers guiding students to memorize the Qur'an? 2. What are the supporting and inhibiting factors of Islamic religious education teachers in guiding students to memorize the Qur'an at SDI Al-Barokah Kramat Tlanakan PamekasanThe method used in this research is field qualitative. As for data collection using interviews with students and teachers, observation and documentation. From this method, researchers process and analyze to arrive at scientific proof. Research result reveal that: The teacher's efforts in guiding students to memorize the Qur'an, namely: correcting student reading when depositing memorization, give examples of reading, repeating what has been memorized, factors that hinder the implementation of teachers in guiding students to memorize Qur'an are : the ability to read and memorize each child is different, less time allocation, some children are not enthusiastic for some reason. In addition to these inhibiting factors, there are also supporting factors, namely : strong motivation or spirit of children, very intensive meetings between teachers and students.